Creative principles o f training as compound didactic bases of vocational training of the teacher of music (Pedagogy of Higher and Secondary Education, 2007)
In article the contents of creative principles of training and education of the teacher of music in a context of a spiritual free choice is proved, the hierarchy of creative principles is allocated on the basis of the concept of integration cognitive and intuitive components of modeling, figurative designs, representation art judgments, methods of extrapolation of ideas of an aesthetics, in conditions of comprehension of modern forms of thinking.
Keywords: teacher of music of a polyart structure; classification of principles of training and education; cognitive senses; creative activity; information culture